Enhancement of solid potato waste treatment by microbial fuel cell with mixed feeding of waste activated sludge. (1st February 2017) - Du, Haixia; Li, Fusheng
Abstract: The effect of mixed feeding of anaerobically cultured waste activated sludge (WAS) on electricity generation of MFC from solid potato waste was investigated by focusing on the major expected role of WAS as an accelerator for hydrolysis of solid potato and a side concurrent role as additional substrate besides solid potato. Columbic efficiency was significantly enhanced from 6.1 to 31.1% when the cultured WAS was mixed at the ratio of 1:4. This effect was associated with the accelerated hydrolysis rate from 0.056 to 0.089 day −1 due to the involvement of bacteria from the WAS. The final utilization of the feedstocks (evaluated by CODCr ) varied within 39.5–89.6%, following the order of potato > mixture of potato & WAS/inactivated WAS > inactivated WAS > WAS. Stable isotope ratio (δ 13 C) analysis indicated that, for the mixed feedstocks, WAS was more easily digested than potato, making the mass fractions of potato and WAS remaining after treatment different from those before treatment. Graphical abstract: Schematic diagram illustrating the effect of waste activated sludge (WAS) on the biological reactions by different bacteria in the anode chamber of MFC for treatment of the solid potato. Highlights: Mixing anaerobically cultured WAS could enhance hydrolysis of solid potato. Enhanced hydrolysis by mixing WAS significantly enhanced electricity generation. Served as substrate, inactivated WAS enhanced electricity generation of solid potato. Organic waste usage followed: potato > mixed potato & WAS > inactivated WAS > WAS. δ 13 C analysis identified mixed feedstock composition remaining after MFC operations.